2017
DOI: 10.1016/j.hbrcj.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Performance appraisal of the A2/O process in domestic wastewater treatment replacing the anaerobic unit with UASB

Abstract: Feasibility of a combined system consisting of an anaerobic up-flow anaerobic sludge blanket (UASB) followed by anoxic unit then aerobic activated sludge (AS) was investigated. The system was fed with normal domestic wastewater, then medium loading wastewater using activated sludge from El Berka WWTP, then high strength sewage having a chemical oxygen demand (COD) of 2635 mg COD/L. The organic loading rate (OLR) was increased gradually from 0.5 to 4.43 kg COD/m 3 /day. The HRT was changed for each loading from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Montalvo et al [47] found that treatment of leachate via UASB was capable of removing 92.4% nitrate, whereas a study conducted by Liu et al [48] reported that leachate treatment by UASB could achieve removal of NH 3 -N, TN and COD as high as 99.3%, 85.4% and 90.3%, respectively. In support of this, Moharram et al [49] also found out that UASB could achieve 50 to 75% of COD removal. Lu et al…”
Section: Up-flow Anaerobic Sludge Blanket (Uasb)mentioning
confidence: 75%
“…Montalvo et al [47] found that treatment of leachate via UASB was capable of removing 92.4% nitrate, whereas a study conducted by Liu et al [48] reported that leachate treatment by UASB could achieve removal of NH 3 -N, TN and COD as high as 99.3%, 85.4% and 90.3%, respectively. In support of this, Moharram et al [49] also found out that UASB could achieve 50 to 75% of COD removal. Lu et al…”
Section: Up-flow Anaerobic Sludge Blanket (Uasb)mentioning
confidence: 75%